Initial Assessment Form of Medical Record Document: Is It Important to Complete? - Zhafira Anisah Kesuma; Nuthea, Merry; Hariyanti, Tita (Fakultas Kedokteran Universitas Brawijaya, 2022)
Medical record document completeness is crucial because it serves as a means of communication, quality evaluation, payment, and legal protection. A preliminary study showed that none of the initial assessment forms in the outpatient unit of Puri Bunda Mother and Child Hospital were filled completely. This study aimed to explore the causes of incomplete initial assessment forms to avoid lawsuits against the hospital. The method used was qualitative research with a case study approach. Data were collected using triangulation, which included in-depth interviews with 15 participants, flow observations, and document studies on 150 medical record files. Data were analyzed using thematic analysis. The document study found none of the medical records with a complete initial assessment form (0%). A total of 141 documents (94%) were not filled at all, and only 9 (6%) of the initial assessment forms were filled in certain fields. The flow observation disclosed that file availability was one of the contributing problems to the completeness of filling. Seven reasons for incomplete initial medical assessment documents were categorized into individual internal and external factors. The internal factors include the lack of awareness of doctors and feeling a high workload, and the external factors include the absence of communication between management and doctors, unavailability of work procedures, the absence of a reward and punishment system, the format and availability of initial assessment forms, and individual culture.